Religious orientation and its relationship to the crisis of social identity - زيدان, حسين حسين (Al-Adab Journal, 2019)
The current research aims to reveal the level of religious commitment among middle school students, and also aims to find differences in the variables of gender (male, female) and academic (scientific, literary) in the level of religious commitment. To find the difference in the variable variables (gender, females) and the academic (scientific, literary) in the level of social identity, and to find the correlation between the two variables of religious commitment and social identity, and to achieve the research goals the research researcher adopted the research (religious commitment of Hamdani, 2011) Social Identity of Saad, 2013) (400) of the students were distributed between (200) males and (200) females and distributors between the scientific branch and the literary branch. The researcher used the statistical bag to handle the statistical data. The results showed that the level of religious commitment in The results of the study also showed a weakness in the level of social identity among middle school students. It also showed that the difference D is statistically significant for males in females at the level of identity The The study also found a positive correlation between religious commitment and social identity. The research reached a number of recommendations, including the identification of some school and social activities that develop the awareness of knowledge towards the direction of social identity. And the research reached a number of proposals, including a pilot study entitled The role of cognitive guidance in the development of religious values ​​among students in junior high school.